The effects of timing and rate of release on population growth of Phytoseiulus persimilis reared on Tetranychus urticae - Stavrinides, Menelaos (My University, 2010)
The purpose of this study was to determine the effects of the timing and rate of release on the population growth of Phytoseiulus persimilis (Acari: Phytoseiidae) reared on bean plants infested with two-spotted spider mite (TSM), Tetranychus urticae (Acari: Tetranychidae). Dwarf bean plants were infested with TSM and 20 P. persimilis females were introduced on each plant 3, 6, 9 and 12 days following TSM infestation. In another experiment, female P. persimilis were introduced at the rates of 5, 10 and 20 per plant 6 days after TSM infestation. The maximum per capita net population growth (MCPG) of P. persimilis was estimated as the maximum number of mobile stages observed on a plant during the course of the experiment divided by the initial number of females released on that plant. Both the timing and rate of release had a significant effect on the MCPG of P. persimilis. Releasing 20 P. persimilis on day nine resulted in an MCPG of 2.97, whereas releases on day 3, 6 or 12 resulted in MCPG values of less than 1.7. In the rate of release experiment, the highest MCPG (4.4) occurred when five female P. persimilis were released per plant, whereas releasing 10 and 20 predatory mites per plant led to MCPG values of 2.71 and 1.66, respectively. The findings indicate that the productivity of a P. persimilis rearing system may be significantly improved through optimization of the timing and/or rate of release. © 2010 Springer Science+Business Media BV.
Keywords: Predator; Prey; Rearing; Two-spotted spider mite